Brain-derived neurotrophic factor – a key player in the gastrointestinal system - Singh, Arjun (Gastroenterology Review/Przegląd Gastroenterologiczny, 2023)
Brain-derived neurotrophic factor (BDNF) is highly expressed throughout the gastrointestinal (GI) tract and plays a critical role in the regulation of intestinal motility, secretion, sensation, immunity, and mucosal integrity. Dysregulation of BDNF signalling has been implicated in the pathophysiology of various GI disorders including inflammatory bowel disease, irritable bowel syndrome, functional dyspepsia, and diabetic gastroenteropathy. This review provides a comprehensive overview of BDNF localization, synthesis, receptors, and signalling mechanisms in the gut. In addition, current evidence on the diverse physiologic and pathophysiologic roles of BDNF in the control of intestinal peristalsis, mucosal transport processes, visceral sensation, neuroimmune interactions, gastrointestinal mucosal healing, and enteric nervous system homeostasis are discussed. Finally, the therapeutic potential of targeting BDNF for the treatment of functional GI diseases is explored. Advancing knowledge of BDNF biology and mechanisms of action may lead to new therapies based on harnessing the gut trophic effects of this neurotrophin.